2017
DOI: 10.2217/rme-2016-0141
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Myeloid Cell-Derived PDGF-B in Neotissue Formation in a Tissue-Engineered Vascular Graft

Abstract: Aim: Inflammatory myeloid lineage cells mediate neotissue formation in tissueengineered vascular grafts, but the molecular mechanism is not completely understood. We examined the role of vasculogenic PDGF-B in tissue-engineered vascular graft neotissue development. Materials & methods: Myeloid cell-specific PDGF-B knockout mice (PDGF-KO) were generated using bone marrow transplantation, and scaffolds were implanted as inferior vena cava interposition grafts in either PDGF-KO or wildtype mice. Results: After 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…They also establish new ECM, predominantly fibronectin, that serves as substrate for EC attachment and migration (27,69). MCs and Mfs are indispensable for vascular graft patency and remodeling, providing key signals for circulating endothelial progenitor cells and ingrowth of anastomotic ECs, as shown in previous studies (15,(46)(47)(48)(70)(71)(72). In a key study, Hibino et al (70) found that Mf infiltration was crucial for neotissue formation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…They also establish new ECM, predominantly fibronectin, that serves as substrate for EC attachment and migration (27,69). MCs and Mfs are indispensable for vascular graft patency and remodeling, providing key signals for circulating endothelial progenitor cells and ingrowth of anastomotic ECs, as shown in previous studies (15,(46)(47)(48)(70)(71)(72). In a key study, Hibino et al (70) found that Mf infiltration was crucial for neotissue formation.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the thicker cellular component of SHV grafts indicates a more robust cellular infiltration, likely due to the presence of VEGF, a well‐known mitogen for ECs and strong chemoattractant for MCs and Mϕs (44, 45). Recruited MCs and Mϕs might have induced robust proliferation of medial‐layer cells (especially smooth muscle cells and fibroblasts) in a well‐orchestrated series of events typical of the wound healing process (15, 4648). Increased cell infiltration was accompanied by reduced thickness of the SIS matrix remaining in the grafts at 1 mo postimplantation, suggesting that SHV grafts remodeled more efficiently than SH grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decellularized tissue engineered constructs have been utilized with increasing frequency and demonstrated improved patency and regeneration potential in pre-clinical studies [1][2][3][4][5][6][7][8][9][10][11][12][13] and clinical trials 14,15 . In addition to decellularized grafts, nonbiological grafts composed of various polymeric biomaterials have also been used to engineer cell-free vascular grafts [16][17][18][19][20][21][22][23][24] . All of these acellular materials must promote endothelialization of the lumen to achieve patency and promote development of the vascular wall through extensive, long-term remodeling.…”
mentioning
confidence: 99%
“…Wash with 0.1% BSA-PBS for 5 min. Incubate in primary antibody with concentrations for keratin 5 (1:1000) 6 , keratin 14 (1:250) 6 and F4/80 (1:100) 7 for 18 h overnight at 4 °C.…”
mentioning
confidence: 99%